Metode Cerita Sebagai Media Penguatan Akhlak Mulia Siswa Pada Mata Pelajaran Akidah Akhlak Kelas VII di Mts Miftahul Ilmiyah Blora - Saputra, Sri Angga Dwi; Ulya Lina, Helina Himmatul; Sa’adah, Latifatus (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The formation of noble morals is the main objective of the Akidah Akhlak subject, in practice, students are still found to reflect less Islamic behavior such as low honesty, lack of respect, and minimal responsibility. This requires the application of learning methods that are able to touch the affective domain. This study aims to describe the implementation of the story method in learning Akidah Akhlak and analyze it in strengthening the noble morals of grade VII students of MTs Miftahul Ilmiyah Blora. The study used a descriptive qualitative approach with subjects of Akidah Akhlak teachers and grade VII students. Data were obtained through observation, interviews, and documentation, then analyzed by data reduction, data presentation, and drawing conclusions. The results of the study indicate that the story method can strengthen students' morals, instill moral values ​​effectively, and form positive attitudes such as honesty, responsibility, and respect. The implementation of this method is done through selecting stories that are relevant to real life, interesting delivery, and reflection on values ​​after the story. In conclusion, the story method is proven to be effective in strengthening students' noble morals because it is able to touch the cognitive, affective, and psychomotor aspects.